Host Factors in the Natural History of Chronic Hepatitis B: Role of Genetic Determinants - null Turyadi; Billy Witanto; Korri E. El-Khobar; M. Luthfi Parewangi; M. Rezki Rasyak; Dhita P. Wibowo; Meta D. Thedja; Irawan Yusuf; Muh. Nasrum Massi; Ilhamjaya Patellongi; Din Syafruddin; David H. Muljono (International Journal of Hepatology)
Background. The host immune system plays an important role in hepatitis B virus (HBV) infection manifestation. Genetic polymorphisms of several inflammatory cytokines, including TNF-α and IL-10, have been associated with chronic hepatitis B (CHB) progression, although with contradicting results. CHB progression can be categorized into four phases, immune tolerance (IT), immune clearance (IC), low/no replicative (LR), and e-negative hepatitis (ENH), with HBeAg seroconversion as an important milestone. Here, we determined the association of TNF-α (rs1800629) and IL-10 (rs1800896 and rs1800872) SNPs in the context of CHB natural history progression, particularly to HBeAg seroconversion, in Indonesian CHB patients. Methods. A total of 287 subjects were recruited and categorized into distinct CHB phases based on HBeAg, viral load, and ALT levels. TNF-α and IL-10 SNPs were determined using PCR-RFLP and confirmed with direct sequencing. The association between SNP genotypes with CHB dynamics was determined using logistic regression presented as odds ratio (OR) with 95% CI. Results. No significant association was found between IL-10 -592A/C polymorphism and progression of IT and IC to LR, IT and IC to ENH, and LR to ENH phases in all the gene models. IL-10 rs1800896 and TNF-α rs1800629 could not be analyzed using logistic regression. Subjects’ age (≥40 years old) was significantly associated with IT and IC to LR (OR: 2.191, 95% CI 1.067–4.578, P=0.034), IT and IC to ENH (OR: 7.460, 95% CI 3.316–18.310, P<0.001), and LR to ENH (OR: 5.252, 95% CI 2.010–14.858, P=0.001). Male gender was associated with LR to ENH (OR: 4.077, 95% CI 1.605–11.023, P=0.004). Conclusions. Age and male gender were associated with CHB phase progression instead of the TNF-α and IL-10 polymorphisms. It would be beneficial to study not only the effect of host determinants but also the viral factor to understand the mechanisms of CHB phase progression.